2016
DOI: 10.1016/j.pcl.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Economic Factors Related to Pediatric Obesity

Abstract: Summary The field of behavioral economics suggests that food and activity choices are governed by costs, available alternatives, and reinforcement. Here, we review basic and translational research using a behavioral economic (BE) framework with overweight or obese children up to age 18. We address BE concepts and methods, discuss developmental issues, the continuum of BE intervention approaches, findings of studies focused on increasing the cost of unwanted behaviors (i.e., energy-dense food intake and sedenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
8
0
2
Order By: Relevance
“…food taxing), to decrease the variety of unhealthy snack options and to decrease the portion size (4,22,48,49) . To increase the consumption of healthy snacks methods other than rewards include subsidies, increasing variety of healthy snack options and making healthy snacks the default option in restaurants and cafeterias (4,22,48,49) . In addition, it also known that individual characteristics influence the difference in RV of healthy foods and unhealthy foods (3,10,21,22) , the effect of rewarding strategies (15) and in general the RV of food (3)(4)(5)8,20) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…food taxing), to decrease the variety of unhealthy snack options and to decrease the portion size (4,22,48,49) . To increase the consumption of healthy snacks methods other than rewards include subsidies, increasing variety of healthy snack options and making healthy snacks the default option in restaurants and cafeterias (4,22,48,49) . In addition, it also known that individual characteristics influence the difference in RV of healthy foods and unhealthy foods (3,10,21,22) , the effect of rewarding strategies (15) and in general the RV of food (3)(4)(5)8,20) .…”
Section: Discussionmentioning
confidence: 99%
“…Epstein et al , Vervoort et al and Jacques-Tiura & Greenwald also suggested that strategies to increase the RV of healthy foods should be combined with strategies to decrease the RV of unhealthy foods. This would increase the chances that people would alter their food choice and consumption habits ( 4 , 22 , 48 ) . Known methods to decrease the consumption of unhealthy snacks are to increase the costs (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha descrito que el exceso de peso y la adiposidad que caracteriza a niños y adolescentes con obesidad, se debe en parte a la presencia combinada de factores genéticos y ambientales, que aunado a la ingestión de energía que excede el gasto y los requerimientos para el crecimiento durante un periodo prolongado de tiempo, hace perentorio profundizar dicha problemática desde diversos enfoques (1,6). En adición a lo anterior, cambios en los patrones dietarios (ingesta de comidas con alto contenido energético, ricos en grasa saturadas y azúcares refinados), como alimentos ultra-procesados y bebidas azucaradas, contribuyen también, al aumento en la prevalencia del exceso de peso en etapas tempranas de la vida (7,8).…”
Section: Introductionunclassified
“…En adición a lo anterior, cambios en los patrones dietarios (ingesta de comidas con alto contenido energético, ricos en grasa saturadas y azúcares refinados), como alimentos ultra-procesados y bebidas azucaradas, contribuyen también, al aumento en la prevalencia del exceso de peso en etapas tempranas de la vida (7,8).…”
Section: Introductionunclassified